Tumor-environment biomimetics delay peritoneal metastasis formation by deceiving and redirecting disseminated cancer cells. (June 2015) - De Vlieghere, Elly; Gremonprez, Félix; Verset, Laurine; Mariën, Lore; Jones, Christopher J.; De Craene, Bram; Berx, Geert; Descamps, Benedicte; Vanhove, Christian; Remon, Jean-Paul; Ceelen, Wim; Demetter, Pieter; et al.
Abstract: Peritoneal metastasis is life threatening and is the result of an extensive communication between disseminated cancer cells, mesothelial cells and cancer-associated fibroblasts (CAF). CAFs secrete extracellular matrix (ECM) proteins creating a receptive environment for peritoneal implantation. Considering cancer as an ecosystem may provide opportunities to exploit CAFs to create biomimetic traps to deceive and redirect cancer cells. We have designed microparticles (MP) containing a CAF-derived ECM-surface that is intended to compete with natural niches. CAFs were encapsulated in alginate/gelatine beads (500–750 μm in diameter) functionalised with a polyelectrolyte coating (MP[CAF]). The encapsulated CAFs remain viable and metabolically active (≥35 days), when permanently encapsulated. CAF-derived ECM proteins are retained by the non-biodegradable coating. Adhesion experiments mimicking the environment of the peritoneal cavity show the selective capture of floating cancer cells from different tumor origins by MP[CAF] compared to control MP. MP[CAF] are distributed throughout the abdominal cavity without attachment to intestinal organs and without signs of inflammatory reaction. Intraperitoneal delivery of MP[CAF] and sequential removal redirects cancer cell adhesion from the surgical wound to the MP[CAF], delays peritoneal metastasis formation and prolongs animal survival. Our experiments suggest the use of a biomimetic trap based on tumor–environment interactions to delay peritoneal metastasis.